Intensitas Penggunaan Smartphone Terhadap Perkembangan Bahasa Anak Usia Dini - Bali, Engelbertus Nggalu; Panmaley, Olgamina; Ndeot, Felisitas (Universitas Nusa Cendana, 2022)
This study aims to find out the relationship between the intensity of device use (Smartphone) and the language development of children aged 3-4 years in Kelapa Lima Village Coconut Lima Rt 027 / Rw 012 Kupang City. The methods carried out in this research are quantitative research with correlational research design. The subject of this study was a total of 3-4 years old children aged in Kelapa Lima Subdistrict of Kelapa Lima Village which amounted to 50 children consisting of 21 boys and 29 girls. The subject-taking method in this study used Purposive Sampling. Data collection tools use questionnaires and documentation using likert scales. Analytical techniques include: normality test and hypothesis tester. The results of the study found that there is a very strong significant relationship between the intensity of smartphone use to the language development of children aged 3-4 years in Kelapa Lima Subdistrict, Kelapa Lima Village Rt 027 / Rw 012 Kupang City. It can be seen from the coefficient between the intensity of the use of gadgets (Smartphones) to the development of the rhitung language = 0.887> r-table = 0367 with a very strong relationship rate with a significant 0.000 < 0.05.